Legal profession in Malaysia: the history - Ali Mohamed, Ashgar Ali; Devaraj, Subash Jai (CLJ Malaysia Sdn. Bhd., 2025)
Being the principal statute regulating the legal profession in West Malaysia, the LPA has, since its inception in 1977 undergone several amendments to suit the changes in the development of the legal profession in the country.6 Having said the above, this Chapter discusses the development of the legal profession and practice in Malaysia.